Identification of polymorphisms in the oocyte‐derived growth differentiation growth factor 9 (GDF9) gene associated with litter size in New Zealand sheep (Ovis aries) breeds. Issue 11 (29th September 2020) - Amirpour Najafabadi, Hamed; Khansefid, Majid; Mahmoud, Ghassan Ghaith; Zhou, Huitong; Hickford, Jon G. H.
Abstract: Having the ability to control litter size is important for sheep farmers and breeders worldwide. However, making genetic gain in key livestock traits like reproductive performance needs typically a lot of time, and both the fecundity and fertility traits have a great economic importance. Attention has therefore turned to better understanding the genes that control reproductive performance. Of these genes, research has focussed on the growth differentiation growth factor 9 (GDF9) gene ( GDF9 ). In this study, a PCR‐single strand conformation polymorphism (PCR‐SSCP) approach was used to investigate variation in this gene in separate groups of purebred Finnish Landrace sheep, Finnish Landrace × Texel‐cross sheep and composite sheep of undefined breed background, but based on New Zealand Romney‐type genetics. Three GDF9 variants (named A, B and C ) were found, and upon DNA sequencing, the nucleotide substitutions c.978A>G, c.994G>A and c.1111G>A were revealed. The frequency of variant A (containing nucleotides c.978A, c.994G and c.1111G) in the Finnish Landrace, Finnish Landrace × Texel‐cross and composite sheep was 0.86, 0.78 and 0.76, respectively. In these three sheep groups, the frequency of B (defined by the presence of nucleotides c.978G and c.994A) was 0.01, 0.03 and 0.23 and for C (containing c.1111A) was 0.13, 0.18 and 0.01, respectively. An animal model was used to estimate the additive effect of fertility data for Finnish Landrace × Texel‐cross sheep and revealed an association between litter size and the c.1111G>A variation ( p = .036), but this was not observed for the Finnish Landrace sheep ( p = .27) or the composite sheep ( p = .17). When all the sheep were analysed together, the presence of c.1111A was associated ( p < .05) with increased litter size, when compared to ewes that had c.1111G. Litter size did not differ between sheep with and without c.994A in all three groups of sheep investigated. This study suggests that c.1111A could be a useful genetic marker for improving fecundity in New Zealand sheep breeds and that it could be introgressed into other breeds, but analysis of more sheep will be required to confirm the associations that have been observed here.